2009
DOI: 10.1007/s10750-008-9682-8
|View full text |Cite
|
Sign up to set email alerts
|

Application of remote sensing to site characterisation and environmental change analysis of North African coastal lagoons

Abstract: This article describes the use of satellite imagery for identifying key environmental characteristics within three North African coastal lagoons (Merja Zerga, Morocco; Ghar El Melh, Tunisia and Lake Manzala, Egypt) and for detecting the major environmental changes within these environments. A combination of Landsat MSS, Landsat TM, Landsat ETM? and ASTER imagery was acquired for the three sites for a period covering the last three decades . Following geometric correction and enhancement, the interpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 44 publications
(69 reference statements)
2
39
0
1
Order By: Relevance
“…This result means that the Manzala lagoon has been heavily impacted by eutrophication caused by wastewater from the drainage system and by the drying processes of land reclamation and urban encroachment due to the expansion of the Dameitta governorate to the east of the lagoon. By comparing the results of this study with other studies (AHMED, et al, 2009), there is general agreement in the trend and pattern of shrinkage for the water surface area of Manzala lagoon. The above situation justifies the creation of improvement works to maintain the present area of the lagoon water body without further area loss.…”
Section: Manzala Lagoonsupporting
confidence: 80%
See 1 more Smart Citation
“…This result means that the Manzala lagoon has been heavily impacted by eutrophication caused by wastewater from the drainage system and by the drying processes of land reclamation and urban encroachment due to the expansion of the Dameitta governorate to the east of the lagoon. By comparing the results of this study with other studies (AHMED, et al, 2009), there is general agreement in the trend and pattern of shrinkage for the water surface area of Manzala lagoon. The above situation justifies the creation of improvement works to maintain the present area of the lagoon water body without further area loss.…”
Section: Manzala Lagoonsupporting
confidence: 80%
“…Their study also indicated that Manzala lagoon has suffered from different levels of eutrophication resulting from human activities and poor management. RAMDANI et al, 2009, stated that zooplankton communities in Manzala lagoon were generally dominated by rotifers and that the planktonic communities were comparatively highly diverse with essentially freshwater species.…”
Section: Introductionmentioning
confidence: 99%
“…1) is the largest coastal lake in Egypt which is a shallow brackish lake extending between the Damietta Nile River branch and the Suez Canal with a maximum length of 50 km along the Mediterranean coast [1]. The northern boundary of the lake is connected with some narrow inlets such as El-Gamil canal with the sea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been gradually transformed from a largely marine or estuarine environment to eutrophic brackish water system. The overall area of the lake was decline from more than 1400 km 2 in the early 1970s to less than 700 km 2 in 2003 [8]. The Lake is considered an important and valuable natural resource ecosystem for fish catch, wildlife, hydrological and biological regime in Egypt.…”
Section: Introductionmentioning
confidence: 99%